2021
DOI: 10.1515/jcim-2020-0283
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combination of Zingiber officinale and Echinacea on alleviation of clinical symptoms and hospitalization rate of suspected COVID-19 outpatients: a randomized controlled trial

Abstract: Objectives Herbal medicines, as a treatment method, have received a great deal of attention. The effects of two herbal medicines namely Zingiber officinale and Echinacea on alleviation of clinical symptoms and hospitalization rate of suspected COVID-19 outpatients were examined. Methods A clinical trial with 100 suspected COVID-19 outpatients as participants was conducted. The participants were allocated randomly to two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“… 49 The results from a clinical trial study from Iran indicate that a combination therapy by ginger and Echinacea in suspected COVID-19 outpatients attenuated some of their clinical symptoms (breath shortness, coughing and muscular pain) in comparison with those treated with a standard protocol using hydroxychloroquine, alone. 50 In addition, the hospitalization rate in the intervention group (2.0%) was lower than that in the control group (6.0%). 50 The results from a randomized-controlled study showed that the patients with ARDS who were fed an enteral diet enriched with ginger extract for 21 days exhibited greater oxygenation, lower serum concentrations of IL-1, IL-6, and TNF-α, and spent shorter time on mechanical ventilation compared to control group.…”
Section: Evidence Of Ginger's Potentials Against Covid-19mentioning
confidence: 84%
See 1 more Smart Citation
“… 49 The results from a clinical trial study from Iran indicate that a combination therapy by ginger and Echinacea in suspected COVID-19 outpatients attenuated some of their clinical symptoms (breath shortness, coughing and muscular pain) in comparison with those treated with a standard protocol using hydroxychloroquine, alone. 50 In addition, the hospitalization rate in the intervention group (2.0%) was lower than that in the control group (6.0%). 50 The results from a randomized-controlled study showed that the patients with ARDS who were fed an enteral diet enriched with ginger extract for 21 days exhibited greater oxygenation, lower serum concentrations of IL-1, IL-6, and TNF-α, and spent shorter time on mechanical ventilation compared to control group.…”
Section: Evidence Of Ginger's Potentials Against Covid-19mentioning
confidence: 84%
“… 50 In addition, the hospitalization rate in the intervention group (2.0%) was lower than that in the control group (6.0%). 50 The results from a randomized-controlled study showed that the patients with ARDS who were fed an enteral diet enriched with ginger extract for 21 days exhibited greater oxygenation, lower serum concentrations of IL-1, IL-6, and TNF-α, and spent shorter time on mechanical ventilation compared to control group. However, organ failure, barotrauma and mortality rate similarly occurred in ginger-treated patients and control group.…”
Section: Evidence Of Ginger's Potentials Against Covid-19mentioning
confidence: 84%
“…One systematic review found a small amount of studies supporting the effectiveness of a number of TCM preparations (Lianhua Qingke granules, Shufeng Jiedu capsule, Jinhua Qinggan granules, Toujie Quwen granules and tailored herbal decoctions) as adjunctive treatments for Covid-19, with 32 ongoing trials identified [9] . Adjunctive treatment with Echinacea and Ginger tablets increased resolution of coughing, muscle pain and breathlessness, in one RCT of 100 outpatients [10] .…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study in outpatients with suspected COVID-19 was conducted in which 50 patients received concurrent Zingiber officinale and echinacea for 7 days in addition to hydroxychloroquine and 50 patients received hydroxychloroquine without supplementation. 16 Improvements in coughing, dyspnea, and muscle pain were higher in the intervention group compared with the hydroxychloroquine alone group, but no other significant differences were observed with respect to other symptoms or hospitalization rates. 16…”
Section: Echinaceamentioning
confidence: 79%